TERAPI RELAKSASI PIJAT PUNGGUNG TERHADAP NYERI TENGKUK PADA PENDERITA HIPERTENSI - Fandani Rada Diva Wardana; Ditte Ayu Suntara (Ensiklopedia of Journal, 2025)
Hypertension is an increase in blood pressure exceeding 140/90 mmHg with at least two measurements at different times. Uncontrolled hypertension can cause serious complications such as stroke, kidney failure, heart failure, metabolic syndrome, and even death. One non-pharmacological effort to control blood pressure is back massage relaxation therapy which aims to relax blood vessels and reduce muscle tension. This study aims to determine the results of nursing care for Mrs. R by applying back massage relaxation therapy to reduce neck pain in hypertension patients in the work area of Sungai Langkai Community Health Center, Batam City. The research method used a case study approach with back massage interventions carried out regularly throughout the study. The results showed a decrease in blood pressure and reduced neck pain after therapy. Back massage works through mechanoreceptor stimulation that triggers the body's relaxation response, increases blood circulation, and stimulates the release of endorphins that play a role in reducing blood pressure and pain. Thus, back massage relaxation therapy is effective as a non-pharmacological nursing intervention to help reduce blood pressure in hypertension patients. Keywords: Hypertension, Relaxation, Back Massage, Neck Pain